The Influence of Service Quality and Business Location on Word of Mouth Through Consumer Satisfaction as a Mediating Variable: Study of Wedangan "Ginastel" Customers in Pemalang City - April Liyan Trio Saputro; Achmad Choerudin; Syahri Alhusin (Digital Innovation : International Journal of Management, 2024)
The objectives of this research are: 1) Test and measure the influence of service quality and business location on consumer satisfaction. (2) Testing and measuring the influence of service quality and business location on consumer Word of Mouth (3) Testing and measuring the influence of service quality and business location through customer satisfaction as a mediating variable. This research was conducted on Wedangan "Ginastel" consumers on Jalan Sulawesi, Mulyoharjo sub-district, Pemalang sub-district, Pemalang City, who actively shop at least 30 consumers every day. Or the monthly average based on 24 working days is 720 consumers. 72 consumers were taken as samples. The research results found that there is an influence of service quality and business location on consumer satisfaction. Service quality and business location influence word of mouth. There is an indirect influence on the relationship between service quality and business location on word of mouth through mediation, namely consumer satisfaction as a mediator.